Quality of Life in Romania 1918–2018: An Overview - Stănescu, Iulian (Calitatea Vieții, 2018)
This paper aims to provide an overview of the quality of life in Romania during the hundred years since the country’s unification in 1918. Three highly relevant domains for the quality of life are reviewed using secondary data analysis: (1) the living standard, with a focus on household income and consumption, (2) living conditions, especially urbanisation, housing and utilities, (3) perceived quality of life. Behaviour, factual, and opinion data was collected from a variety of sources: statistical and social surveys, census data, official statistics, archive documents, and academic research. The periodisation is based on the two major historical events that shaped Romanian history from 1918–2018: the Second World War and the December Revolution of 1989, resulting in four discrete blocks: the interwar years (1919–1939), the Second World War and first post-war years (1940–1947), the period of the communist regime (1948–1989), and the period following the Romanian Revolution of 1989.